1964
DOI: 10.1254/jjp.14.256
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ganglionic Blocking Agents on Responses of Ductus Deferens Preparation of Guinea-Pig to Hypogastric Nerve Stimulation

Abstract: The sympathetic nature of the hypogastric innervation of the ductus deferens of guinea-pig has been concluded by Hukovic (1) from the results that the contractile response of the isolated ductus deferens to stimulation of the hypogastric nerve is en hanced by the addition of noradrenaline and is abolished by the previous reserpiniza tion of the animal. In the same line Boura et al. (2) (5) have demonstrated the enhancement of the response by the addition of eserine and various adrenolytics. The potentiating ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1970
1970
1988
1988

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 4 publications
(4 reference statements)
0
1
0
Order By: Relevance
“…Many investigators have reported that the addition of noradrenaline into the bath augmented the contractile response of the vas deferens to hypogastric nerve stimulation (1,12,13). The intravenous injection of noradrenaline also augmented both the electrical and mecha nical responses to hypogastric nerve stimulation 10 minutes after the drug administration, but the degree of the augmentation of the responses was not so dramatic compared with that of the in vitro preparation (Fig.…”
Section: Effect Of Noradrenalinementioning
confidence: 92%
“…Many investigators have reported that the addition of noradrenaline into the bath augmented the contractile response of the vas deferens to hypogastric nerve stimulation (1,12,13). The intravenous injection of noradrenaline also augmented both the electrical and mecha nical responses to hypogastric nerve stimulation 10 minutes after the drug administration, but the degree of the augmentation of the responses was not so dramatic compared with that of the in vitro preparation (Fig.…”
Section: Effect Of Noradrenalinementioning
confidence: 92%